Chronic kidney disease in patients with psoriasis -A hospital based cross sectional study - P Seena; Sandhya George; Beena Narayanan; M Poornimamba; C V Shabna; Ajith Gopinath (Wolters Kluwer Medknow Publications, 2021)
Background: Psoriasis is a multi-system inflammatory disease where skin and joints are the primary targets. Recently, some studies had shown the association of psoriasis with kidney disease. Aims: To study the association of psoriasis with chronic kidney disease (CKD) in a tertiary health care center. Methodology: The study was conducted in the Department of Dermatology in a tertiary care center in Kerala. The study was a descriptive cross-sectional study for 6 months from August 2017 to January 2018. A total of 104 patients with psoriasis were studied. Clinical data was collected. Glomerular filtration rate (GFR) and albumin creatinine ratio (ACR) were found out to know the presence of CKD. Descriptive and inferential statistical analysis has been carried out in the present study. Observations: Of the 104 patients, 14 were diagnosed as having CKD. Of the 14 CKD patients, 12 had severe psoriasis, 2 had moderate psoriasis, and none had mild psoriasis. The risk factors for CKD (presence of diabetes mellitus/hypertension or intake of drugs-non-steroidal anti-inflammatory drugs [NSAIDs]/cyclosporine) were present in 9 out of 14 CKD patients. The duration of psoriasis was more than 10 years in 10 CKD patients. Conclusion: Our study demonstrated that psoriatic patients have an increased risk of developing CKD and this risk is found to increase with the severity and duration of psoriasis. Our results require confirmation in large-patient populations in prospective studies or case-control studies.